CARDIOPROTECTIVE EFFECT OF INDIGOFERA TINCTORIA LINN. AGAINST MYOCARDIAL INFARCTION-INDUCED RATS - P, Shankaraiah; K, Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The aim and objective of the present study are to study the protective effects of ethanolic extract of Indica tinctoria (EEIT) in isoproterenol-induced acute myocardial infarction (AMI) in rats. Methods: The effect of two doses of isoproterenol (5 mg/kg and 8.5 mg/kg body weight) changes in aspartate transaminase (AST), alanine transaminase (ALT), lactate dehydrogenase (LDH), creatine phosphokinase (CPK), and total protein (TP) and lipid hydroperoxides, superoxide dismutase (SOD), and glutathione (GSH) in blood serum and heart homogenate, for the two consecutive days (29 and 30), were administered subcutaneously in rats in pre-treatment with EEIT for the 28-day study. Results: There was increased the AST, ALT, LDH, CPK, and lipid peroxides levels and decreased the TP, SOD, GSH with Isoproterenol-induced group. Pre-treatment for 28 days with Indigofera tinctoria significantly (p<0.05) increased antioxidants (SOD , GSH) , TP levels and decreased the cardiotoxic agents significantly (p<0.05) such as LPO, AST, ALT, LDH, and CPK levels in treatment groups. Conclusion: I. tinctoria contains beneficial bioactive photochemicals that have been protective effective against isoproterenol-induced AMI in rats.